Social representations of big data and artificial intelligence. A structural exploration. - Becerra, Gastón; Lopez Alurralde, Juan Pablo (Cultura y Representaciones Sociales, 2022)
Summary. This work seeks to explore the social representations of big data and artificial intelligence. A survey was carried out with a word association technique, with Argentine university students and recent graduates of different branches of knowledge (N = 335 for big data and 255 for artificial intelligence). We explore the meanings to which both phenomena are associated, the structure of their representation, the similarities and differences between them and with other phenomena, the possible themes that are inferred, and the possible differential positions of the groups. The results indicate the predominance of senses linked to information (big data) and robots (AI), coexisting with positively valued notions, such as knowledge, and with references to negatively valued social problems, such as unemployment and social control.